Glassy behaviour of mechanically amorphised ZIF-62 isomorphs. Issue 73 (23rd August 2021) - Thorne, Michael F.; Sapnik, Adam F.; McHugh, Lauren N.; Bumstead, Alice M.; Castillo-Blas, Celia; Keeble, Dean S.; Diaz Lopez, Maria; Chater, Phillip A.; Keen, David A.; Bennett, Thomas D.
Abstract : Zeolitic imidazolate frameworks (ZIFs) can be melt-quenched to form glasses. Here, we present an alternative route to glassy ZIFs via mechanically induced amorphisation. Abstract : Zeolitic imidazolate frameworks (ZIFs) can be melt-quenched to form glasses. Here, we present an alternative route to glassy ZIFs via mechanically induced amorphisation. This approach allows various glassy ZIFs to be produced in under 30 minutes at room temperature, without the need for melt-quenching.